Strategi Guru Meningkatkan Keterampilan Kerfikir Kritis Siswa Melalui Litersi Digital dalam Pembelajaran IPS - Natasya Himelza; Buchori Nurdin; Wibi Wijaya (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
This research was motivated by students’ difficulties in completing tasks that require analytical and evaluative thinking, as well as in formulating questions or justifying their answers during social studies learning. The study aims to (1) analyze teachers’ strategies in enhancing students’ critical thinking skills through digital literacy, (2) examine the implementation of digital literacy in social studies learning, and (3) explore its impact on students’ critical thinking at SMPN 25 Padang. This study employs Jean Piaget’s constructivist cognitive learning theory with a qualitative descriptive approach. Data were collected through observation, interviews, and document studies, involving six informants selected purposively. The data were analyzed using Miles and Huberman’s steps of data reduction, data display, and conclusion drawing. The results show that teachers enhance students’ critical thinking by integrating digital literacy into learning, promoting the analysis of online information, applying Problem-Based Learning (PBL), facilitating discussions, and giving constructive feedback. Digital literacy is implemented through teaching modules that utilize digital sources and platforms. Its impact includes greater student engagement, improved collaboration, and strengthened critical thinking skills. However, challenges such as information overload and technology dependency need careful attention. Overall, digital literacy is perceived as an effective and enjoyable approach to social studies learning.